Participatory Arts-Based Pedagogy in Baccalaureate Nursing Education. Issue 1 (15th January 2022) - Raber, Anjanette M.; Vermeesch, Amber
Abstract: Arts-based pedagogy (ABP) is an innovative teaching method combining art and learning in an existing curriculum. To understand the impact of students' perceptions of the effects of ABP on critical thinking, communication, and observational skills, 89 students completed an online survey. The results indicate that students enjoyed ABP and that it positively affected critical thinking, enhancing their future clinical practice and preparing them for increasingly complex health care environments.